GAMBARAN GOUT ARTRITIS YANG DI SEBABKAN OLEH HIPERURISEMIA DI POLIKLINIK PENYAKIT DALAM DAN RADIOLOGI RSUD MEURAXA - Said Aandi Saida; Fuziati Fuziati (Jurnal Sains Riset, 2021)
Gout Arthritis is a group of heterogeneous diseases as a result of deposition of crystals of monosodium veins (C5H4N4O3) in tissue or as a result of supersaturation of uric acid in the extracellular fluid. One of the metabolic disorders that cause gout arthritis is Hyperurisemia, defined as elevated uric acid levels over 7.5 ml / dl in males and 6.5 ml / dl in females. This study aims to determine the description of Gout Artritis caused by hyperuricemia in polyclinic internal disease and radiology Regional Hospital Meuraxa Banda aceh Year 2017. This study is observational analytic with a sample amounting to 43 people who are done by way of diagnosis of doctors in the disease, Patient history and medical redord. In general, the results showed that the Gout Arthritis picture caused by hyperuricemia in polyclinics of internal medicine and radiology of RSUD Meuraxa Banda aceh in 2017 was obtained by gender based on 31 patients (72,1%), Age was age 65 years with total 16 patient (37,2%). Gout Arthritis is closely related to hyperuricemia because of 20 people with high uric acid levels (8 ml / dl in men and 7 ml / dl in females) 19 of whom suffer from Gout Arthritis. From the statistical results show that the average value obtained is p count = 0.01 (p 0.05). These results indicate that there is a relationship between hyperuricemia and Gout Arthritis incidence.Keywords: Gout Artritis, Hiperuricemia